Implementation of Penal Mediation "Tepung Tawar" as Criminal Case Settlement in Palembang, South Sumatra - Junaidi, Junaidi (Teumulong: Journal of Community Service, 2024)
Legal pluralism in Indonesia makes it a dynamic legal dynamic. Conflict resolution in social relations, whether it is a civil or criminal matter in Indonesian customary society prefers to be resolved by family or deliberation. In the settlement of criminal cases in Palembang, there is a customary tradition known as "tepung Tawar". This dispute resolution ends with "berangkan-angkanan" (binding brotherhood) which indicates that both parties have reached a consensus/agreement. In writing this Community Service article I will discuss the implementation of the customary tradition of "tepung tawar" in Palembang, South Sumatra Province, this activity aims to provide understanding to the community about restorative justice by means of "tepung tawar" as a medium for conflict resolution.